THE EFFECT OF INFORMATION SYSTEMS, COMMUNICATIONS AND CAREER DEVELOPMENT TO COMMITMENT IN MARITIME HIGHER EDUCATION INSTITUTE JAKARTA - Rosmayana Rosmayana (Program Studi S3 Ilmu Manajemen, 2017)
This study aimed to determine the effect of system information, communications and career development of commitment to lecturer Maritime Higher Education Institute of Jakarta. This study uses a quantitative approach with survey methods and data analysis techniques using correlation analysis and path analysis (path analysis).Discussion: Affordable population in this study is a lecturer in Maritime Higher Education Institute of Jakarta with samples of 108 lecturer in Technique proportional random sampling of each program of study Maritime Higher Education Institute of Jakarta.The results showed that: (1) there is a direct positive influence on the commitment of information system; (2) there is a direct positive influence on the commitment of communication; (3) there is a direct positive influence on the commitment of career development; (4) there is a direct positive influence on information systems, communications, and career development together against of commitments.Keywords: Information System, Communication, career Development and Commitment